Gut Microbiota and Infant Colic: is there a Place for Prebiotics, Probiotics, and Postbiotics? - Melisa Puntillo; Romina Mehaudy; Gabriel Vinderola (Revista del Hospital Italiano de Buenos Aires, 2023)
The consumption of probiotics, prebiotics, and postbiotics, or a combination of them, can contribute to maintaining a healthy intestinal microbiota as it allows the regulation of its dysbiosis in the case of some diseases or disorders, mainly in functional gastrointestinal disorders (FGIDs). The gut microbiome is an essential player in the pathophysiology of FGIDs through its metabolic and nutritional functions, the maintenance of intestinal mucosal integrity, and the regulation of the immune response. Research results thus far indicate that probiotics, prebiotics, and postbiotics may have direct and clinically relevant immunomodulatory effects. There is evidence regarding the prescription of this family of biotics in healthy individuals to improve overall health and alleviate symptoms in many conditions like infantile colic. The colonization and microbiota establishment begins at birth; the first 2-3 years of life are critical for developing an abundant and diverse microbial community. Several scientific studies performed by traditional culture-dependent techniques and more recently by molecular techniques have observed differences in the bacterial populations of healthy infants and those suffering from FGIDs, the latter characterized by an increase in pathogenic species and a lower population of bifidobacteria and lactobacilli, compared to the former. In this context, the intestinal microbiota plays a leading role in the onset of these disorders, including infantile colic, through its metabolic and nutritional functions, maintenance of the integrity of the intestinal mucosa, and regulation of the immune response. That has opened the door to the study of prebiotics, probiotics, and postbiotics usage in the treatment and or prevention of infantile FGIDs. Vaginal and term delivery and breastfeeding are fundamental in the constitution of a healthy microbiota. As supportive tools, there are efficacy studies that support the administration of this family of biotics, mainly in cases where lactation is not possible or is limited.